Exchange-coupling in thermal annealed bimagnetic core/shell nanoparticles - Lavorato, Gabriel Carlos (2015)
In this study we demonstrate that the effective coupling of the magnetic phases in core/shell nanoparticles can be promoted by an appropriate thermal annealing. In this way, the magnetization thermal stability of the hard ferrimagnetic CoFe2O4 oxide can be increased up to room temperature when coupled to a CoO antiferromagnetic core in an inverse core/shell structure. In addition, the results show that, being encapsulated in a ∼2 nm thick CoFe2O4 shell, the CoO core is successfully protected against oxidation which is crucial for the effectiveness of the magnetic coupling at the interface.